2016
DOI: 10.1371/journal.pone.0152198
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and Blood Pressure Trajectory during Pregnancy in Relation to Vitamin D Status

Abstract: Every tenth pregnancy is affected by hypertension, one of the most common complications and leading causes of maternal death worldwide. Hypertensive disorders in pregnancy include pregnancy-induced hypertension and preeclampsia. The pathophysiology of the development of hypertension in pregnancy is unknown, but studies suggest an association with vitamin D status, measured as 25-hydroxyvitamin D (25(OH)D). The aim of this study was to investigate the association between gestational 25(OH)D concentration and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Our study showed that pregnant women with GH and healthy controls did not differ significantly in terms of their 25(OH)D concentrations (18.20 ng/mL vs. 22.10 ng/mL, p = 0.1481), and serum 25(OH)D has not been identified as a significant predictor of GH on either logistic regression analysis or ROC analysis. These observations are consistent with the results published by Bärebring et al [13] who demonstrated that vitamin D status correlates significantly with blood pressure during the first trimester and gestational systolic blood pressure trajectory, but not with the prevalence of GH. The relationship between vitamin D status and GH has also been a subject of other studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed that pregnant women with GH and healthy controls did not differ significantly in terms of their 25(OH)D concentrations (18.20 ng/mL vs. 22.10 ng/mL, p = 0.1481), and serum 25(OH)D has not been identified as a significant predictor of GH on either logistic regression analysis or ROC analysis. These observations are consistent with the results published by Bärebring et al [13] who demonstrated that vitamin D status correlates significantly with blood pressure during the first trimester and gestational systolic blood pressure trajectory, but not with the prevalence of GH. The relationship between vitamin D status and GH has also been a subject of other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Our results presented here, obtained in a cohort of pregnant Polish women, are consistent with previously reported findings [32]. According to Barebring et al, at least a 30 nmol/L increase in serum 25(OH)D concentration is associated with lower odds of PE, regardless of vitamin D status in early pregnancy [13]. Similar to our study, these authors found an inverse association between the occurrence of PE and serum concentration of 25(OH)D during the third trimester.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Sweden, approximately 3% of pregnancies are complicated by preeclampsia [6] and just below 5% of singletons are born prematurely [7]. We have previously shown that 25-hydroxyvitamin D (25(OH)D) concentrations in the third trimester and changes in 25(OH)D during pregnancy are associated with lower odds of preeclampsia [8]. …”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, vitamin D influences calcium and phosphorous homeostasis (6) to enable fetal bone mineral accretion. More recent evidence however, suggests that maternal serum 25(OH)D levels may also influence extra-skeletal maternal and fetal health outcomes; including birthweight and the risk of pre-eclampsia (PET), gestational diabetes mellitus (GDM), pre-term birth and small for gestational age (SGA) (6,7) .This observational study examined maternal vitamin D intakes in the first trimester. Women were recruited at their convenience after sonographic confirmation of a singleton pregnancy in the first trimester.…”
mentioning
confidence: 99%